The survey of chromium (VI) Adsorption from aqueous solutions by powder and activated Carbon Pine Cones - Fahimeh Sharifan; Ali Shahidi; Abbas Khashei (Mashhad University of Medical Sciences, 2017)
Background& objective: The hexavalent chromium is a toxic and water-soluble heavy metal that is absorbed and stored through the digestive system and through the skin in the human body. That amount is exceeded in drinking water in Birjand. So the purpose of this studies, Process about remove the hexavalent chromium by using from pine fruit powder, carbon and compare to each other. Methods: In this research, for Calculate removal efficiency (Re), Parameters of contact time, pH, adsorbent dose, initial Cr (VI) concentration and Temperature was studied. Experiments were intermittently performed in batch reactor on Shaker. Results: The results showed that the absorption of chromium significantly depends on the pH of the solution and the absorption rate in the range of 3 for powder and 1 for carbon was achieved when the pH of the solution. The maximum removal of Cr (VI) for pine fruit powder is 96/5 % and for activated Carbon Pine Cones is 93/958%. The results indicate that the soluble chromium ions through the absorbent used in this study, as well as follow the Langmuir isotherm model. Conclusion: The most remove of the hexavalent chromium happened by pine fruit powder and Pine cones can be used as an effective and inexpensive method to remove of the hexavalent chromium from contaminated wastewater.